Tumor granulosa cells of the ovary, associated with pregnancy - Brock, Donal (2015)
One of the ovarian tumors feminizing generally true associated with sterility, the tumor is granulosa cells, because the tumor hiperestrinismo produced by pituitary prevents ovulation inhibition; however they exist in the literature 22 cases of tumor granulosa cells associated with pregnancy, to which the author adds his own experience.